Pacing and opponents: the regulation of exercise intensity during competition - Konings, M. J. (School of Sport, Rehabilitation and Exercise Sciences, University of Essex, 2018)
The goal-directed regulation of the exercise intensity over an exercise bout has been shown to be an essential determinant for performance. During their competition, exercisers are required continuously to make decisions about how and when they are going to invest their limited available energy resources. The regulation of the exercise intensity is an intriguing area of sport science research, and a complex one as demonstrated by the multitude of different theories regarding pacing that are around attempting to explain how this is done. Previous research revealed optimal pacing strategies in time trial exercise and the importance of feedback regarding the internal bodily state. The present thesis adds onto this knowledge by highlighting the external world around the exerciser and its effect on pacing. This has been done by focusing on arguably the most important external variable in competitions: the opponent. It has been shown how opponents could invite exercisers to adjust their pacing behaviour in real-life competitions and in controlled laboratory situations. Moreover, it has been illustrated that even the same opponent could evoke different pacing responses and alter the information-seeking behaviour, depending on the competitive situation that is presented towards the exerciser. It has been demonstrated how an accumulation of preceding race efforts could impact the pacing and performance of elite athletes during their competition. Finally, the reciprocal interaction in pacing decision-making between the effect of an opponent and the internal state of the exerciser was demonstrated, providing novel insights into the regulatory mechanism of exercise regulation. The present findings of this thesis emphasizes the importance of what is happening around the exerciser for the outcome of the decision-making process involved in pacing, and highlight the necessity to incorporate human-environment interactions into models that attempt to explain the regulation of exercise intensity.